EFEKTIFITAS PELAYANAN BEKANG AKMIL DALAM MENDISTRIBUSIKAN KAPORLAP TARUNA TINGKAT IV AKADEMI MILITER - Sulistyowati, Sri; Endang, Rini; Siregar, Paulina (PPM Sdirjianbang Akademi Militer, 2024)
The Military Academy is an educational institution of the Indonesian Army that trains officer candidates with the Three Basic Patterns, namely good academics, strong character, and excellent physical fitness, supported by facilities and infrastructure at the Military Academy that are closely tied to the support services of the Military Logistics in effectively aiding the service and distribution of logistical supplies to the cadets, ensuring that the learning and training activities of the cadets meet expectations. However, there are often issues with the receipt of Kaporlap that are not in accordance and the delays in the distribution of Kaporlap, which hinder the learning and training activities of the fourth-level cadets at the Military Academy. This research was conducted to determine whether the services provided by Bekang Akmil in distributing Kaporlap have been effective or not. This research was conducted using a descriptive qualitative method, obtaining data from interviews and documents, as well as data analysis through data triangulation, which includes data reduction, data presentation, conclusion drawing, and verification. The acceptance of the Kaporlap experienced by the fourth-year cadets has not been satisfactory, as indicated by the discrepancies between the Kaporlap received and what has been recorded by the cadets, as well as the delays in the distribution of the Kaporlap. The effectiveness of the Bekang Akmil service greatly influences the distribution of Kaporlap to cadets. So far, the service and distribution provided by Bekang Akmil have been effective; however, the issues that often arise are beyond the authority and responsibility of Bekang Akmil.